Socio-economic factors that affect the academic performance in university students of the Humanities Faculty of the Universidad Autónoma de Baja California - Armenta, Nereyda G. (2008)
In the present investigation one tries to know about what way they affect the socioeconomic factors in the academic performance of the university students of the faculty of human sciences of the UABC, with the aim to determine which is the reason of the low academic performance. I work with a sample of 60 students to which apply a survey that consists of 21 questions of multiple option. The obtained results show that the raised hypotheses are void since none of the factors affects the academic performanc of the university students.